The end of the line: Antagonistic attentional weightings in unilateral neglect. (October 2018) - McIntosh, Robert D.
Abstract: The line bisection task is widely used in the study of neglect. Some years ago, McIntosh, Schindler, Birchall, & Milner (2005) proposed a radical reframing of this ubiquitous task. Rather than using the traditional measure of directional bisection error, they quantified the sensitivities of the response to the changing locations of the left and right endpoints of the line, expressing these as 'endpoint weightings'. A novel prediction generated from their analysis was that manipulations increasing attention to the left end of the line should cause an increase in the left endpoint weighting and a corresponding reduction in the right endpoint weighting. The present study fulfilled this prediction, using a forced-report cueing method in a group of 12 patients with left neglect. The data confirm an antagonistic relationship between endpoint weightings, consistent with the idea that they represent the sharing of a finite resource. It is argued that the endpoint weightings model of line bisection offers a sensitive and uniquely useful framework for studying competitive lateral biases of attention in neglect, and may also provide insight into non-lateralised attentional impairments.